Coexistence of Cloud Technology and IT Infrastructure in Higher Education - Riliskis, Laurynas; Osipov, Evgeny (2013 IEEE Frontiers in Education Conference (FIE), 2013)
Most of the current IT-infrastructures at Universities were designed and deployed at times of mostly campus based education, following the "one solution fits all" approach. Nowadays, with the growing number of courses given on distance and unique requirements on software content in almost every course in all disciplines the existing infrastructure became extremely stiff and inefficient. In many cases it fails providing flexible services with acceptable quality both to teachers and students. Another problem appears with the all growing mobility of students in the scope of Erasmus Mundus programme and numerous bilateral agreements between universities. The uncertainty in number of students to be handled in each semester (even in the scope of a particular course) makes it difficult for the IT departments to estimate the need and to correspondingly dimension the IT-system. Normally, IT administrations at universities over-dimension their infrastructures in order to stay competitive and provide satisfactory quality of experience. This obviously leads to an increased cost associated with purchasing and maintaining the equipment. Besides the economical component the environmental impact becomes one of the critical factors that universities have to deal with nowadays. Universities as governmental organizations need to take environmental considerations into account when implementing European Union policies on ICT sustainability. Cloud technology and specifically infrastructure as a service (IaaS) providers is an excellent alternative to an outdated inefficient local infrastructures. Early 2012 Luleå University of Technology started a project on adopting cloud technology for implementing the university's IT-infrastructure. This work-in-progress article will describe the results of its pre-study phase aiming at understanding a feasibility of integrating and/or migrating key infrastructure components into an IaaS system and opening ways for making university's resources more accessible to wider public. Numbers of ...